Augmenting Alzheimer's Research: Schol‐AR. (31st December 2021) - Ard, Tyler; Toga, Arthur W.
Abstract: Background: The multi‐disciplinary field of Alzheimer's disease research relies on many modern forms of data, from neuroimaging volumes and cellular image‐stacks to population and genetic information. Unfortunately, much of this information is difficult to communicate through the standard communication of scientific articles and static images, often resulting in incomplete data reporting and suboptimal comprehension for many readers. Method: We introduce an augmented reality technique to layer modern digital information ontop of printable scientific figures, enabling full datasets to be attached to scientific articles. This system is additionally paired with an uploading framework that allows authors to create and disseminate augmentations from their own data. Result: The capabilities provided through both the augmented viewing and augmentation creating systems facilitate communication and comprehension of the complex information underlying Alzheimer's research. Conclusion: Augmented reality technologies can improve and modernize the state of scientific communication in Alzheimer's research, bridging the gap between modern digital data and journal article communications.